Boron Adsorption Kinetics of Microcrystalline Cellulose and Polymer Resin - Raval, Parth (Langmuir : the ACS journal of surfaces and colloids, 2023)
Tailoring boron-polysaccharide interactions is an important strategy for developing functional soft materials such as hydrogels, fire retardants, and sorbents for environmental remediation, for example, using lignocellulosic biomass. For such applications to be realized, it is paramount to understand the adsorption kinetics of borate anions on cellulose and their local structures. Here, the kinetic aspects of boron adsorption by microcrystalline cellulose, lignin, and polymeric resin are investigated and compared. Borate anions interact with the vicinal diols in the glucopyranoside moieties of cellulose to yield chemisorbed boron chelate complexes. In contrast to cellulose, technical lignin contains fewer cis-vicinal diols, and it does not have a tendency to form such chelate complexes upon treatment with the aqueous boric acid solution. The formation kinetics and stability of these chelate complexes strongly depend on nanoscale structures, as well as reaction conditions such as pH and concentration of the sorbate and sorbent. Specifically, insights into the distinct boron adsorption sites were obtained by solid-state one-dimensional (1D) 11B magic-angle spinning NMR and the local structures and intermolecular interactions in the vicinities of boron chelate complexes are elucidated by analyzing two-dimensional (2D) 1H-13C and 11B-1H heteronuclear correlation NMR spectra. The total boron adsorption capacity of cellulose is estimated to be in the 1.3-3.0 mg range per gram of sorbent, which is lower than the boron adsorption capacity of a polystyrene-based resin, ∼17.2 mg of boron per gram of Amberlite IRA 743. Our study demonstrates that the local backbone and side chain flexibility as well as the structures of polyol groups play a significant role in determining the kinetic and thermodynamic stability of chelate complexes, yielding to different boron adsorption capabilities of lignocellulosic polymers